2018
DOI: 10.1038/s41467-018-04467-3
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-templated nanofiltration membranes for ultrahigh performance desalination

Abstract: Nanofiltration (NF) membranes with ultrahigh permeance and high rejection are highly beneficial for efficient desalination and wastewater treatment. Improving water permeance while maintaining the high rejection of state-of-the-art thin film composite (TFC) NF membranes remains a great challenge. Herein, we report the fabrication of a TFC NF membrane with a crumpled polyamide (PA) layer via interfacial polymerization on a single-walled carbon nanotubes/polyether sulfone composite support loaded with nanopartic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
338
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 512 publications
(348 citation statements)
references
References 57 publications
(51 reference statements)
9
338
0
1
Order By: Relevance
“…The introduction of ferrofluid opens a new avenue in nanoscale flow regulation, by simultaneously providing a shapeable liquid–hydrophilic interface that enables excellent gating performance. The versatility and easy fabrication of the nanofluidic, which may benefit many practical applications such as microfluidic system and seawater desalination devices, hold promise for mass production. This work can be further generalized to other nanoscale pores for the exploitation of smart membrane materials, ranging from nanoscale reactors, chemical separations, and battery membrane to drug delivery, medical devices, and sensors for bioassays.…”
Section: Methodsmentioning
confidence: 99%
“…The introduction of ferrofluid opens a new avenue in nanoscale flow regulation, by simultaneously providing a shapeable liquid–hydrophilic interface that enables excellent gating performance. The versatility and easy fabrication of the nanofluidic, which may benefit many practical applications such as microfluidic system and seawater desalination devices, hold promise for mass production. This work can be further generalized to other nanoscale pores for the exploitation of smart membrane materials, ranging from nanoscale reactors, chemical separations, and battery membrane to drug delivery, medical devices, and sensors for bioassays.…”
Section: Methodsmentioning
confidence: 99%
“…Among recently reported ultrathin membranes, the most promising materials for OSN are the PA and DLC membranes 2,11. It is worth noting that ultrathin PA membranes are also widely used for water filtration 12–19. Other promising ultrathin membranes for water filtration include those constructed by proteins,7 single‐walled carbon nanotubes (SWCNT),21–24 metal oxide nanowires,25,26 metal hydroxide nanostrands,27–30 graphene nanosheets,31,32 graphene oxide (GO) nanosheets,33–38 WS 2 nanosheets,40 and MoS 2 nanosheets 41…”
Section: For Liquid Filtrationmentioning
confidence: 99%
“…Aside from OSN, TFC membranes are also widely used in water desalination and wastewater purification 12–19. Because the PA active layer determines the separation performance of the TFC membrane, the construction of an ultrathin and high‐quality PA active layer is critical for producing an advanced TFC membrane with high water permeance and solute rejection.…”
Section: For Liquid Filtrationmentioning
confidence: 99%
See 1 more Smart Citation
“…These NF were tested for methyl blue model compound which gave high rejections up to 99.6% with a permeance of 33.0 L m −2 h −1 bar −1 . Wang et al[231] reported the fabrication of PA/CNT NF membranes with ultrahigh permeability and high rejection. The active layer was formed through interfacial polymerization on an UF support embedded with ZIF-8 nanoparticles.…”
mentioning
confidence: 99%